Fostering positive spaces in public health using a cultural humility approach. Issue 4 (14th April 2019) - Allwright, Kathryn; Goldie, Catherine; Almost, Joan; Wilson, Rosemary
Abstract: Culturally competent frameworks used within health care systems are contributing to the discrimination and marginalization of sexually and/or gender diverse persons. In this discursive paper, we argue that cultural humility ought to be implemented as the best practice approach for fostering sexually and gender diverse positive spaces in public health settings. A paradigm shift away from cultural competence frameworks toward cultural humility is necessary. This shift can be achieved by enhancing educational opportunities for public health nursing students and professionals and by recruiting organizational leaders to be champions for systemic change. In order to achieve this, we must establish effective educational programs that espouse cultural humility practices and develop valid measurement tools for assessing the provision of culturally humble care. This would equip educators, students, practitioners, and organizational leaders with the necessary tools to guide and assess their performance. Integrating a culturally humble approach will ultimately enhance self‐reported cultural safety in public health spaces and reduce health inequities experienced by sexually and/or gender diverse clients and staff members.